2018
DOI: 10.1029/2018ms001302
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Hybrid Usage of a Cumulus Parameterization Scheme on Tropical Convection and Large‐Scale Circulations in a Global Cloud‐System Resolving Model

Abstract: The impact of activating a cumulus parameterization scheme in the global nonhydrostatic icosahedral atmospheric model (NICAM) coupled with a one‐dimensional (1‐D) mixed‐layer ocean model is assessed using a cloud‐system‐resolving, 14‐km mesh. The Chikira‐Sugiyama (CS) scheme, which employs an entrainment rate sensitive to the humidity of the environment, can consider congestus clouds in the tropics when used in conventional global climate models. Congestus clouds are underresolved in the default 14‐km mesh NIC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 75 publications
(91 reference statements)
0
9
0
Order By: Relevance
“…The land surface model, Minimal Advanced Treatments of Surface Interaction and RunOff (MATSIRO) (Takata et al, 2003) solves land states such as soil temperature, soil moisture, and land surface fluxes. Ocean surface fluxes are calculated following Louis (1979) with a modified roughness length for strong surface wind conditions (Fairall et al, 2003;Moon et al, 2007). The conventional orographic gravity wave drag scheme (McFarlane, 1987) is used to introduce the effect of vertically propagating subgrid-scale orographic gravity waves on the momentum tendency of the atmosphere.…”
Section: Overviewmentioning
confidence: 99%
“…The land surface model, Minimal Advanced Treatments of Surface Interaction and RunOff (MATSIRO) (Takata et al, 2003) solves land states such as soil temperature, soil moisture, and land surface fluxes. Ocean surface fluxes are calculated following Louis (1979) with a modified roughness length for strong surface wind conditions (Fairall et al, 2003;Moon et al, 2007). The conventional orographic gravity wave drag scheme (McFarlane, 1987) is used to introduce the effect of vertically propagating subgrid-scale orographic gravity waves on the momentum tendency of the atmosphere.…”
Section: Overviewmentioning
confidence: 99%
“…We generated the initial parameter ensemble by independent random numbers from a Normal distribution whose mean B 1,default and SD B 1,spread are 0.10 and 0.05, respectively (cf. Miyakawa et al (2018) showed that the parameters in a cumulus parameterization scheme were sensitive to precipitation bias in NICAM. The experimental results are verified with observed LWP, OLR, and OSR.…”
Section: Experimental Settingsmentioning
confidence: 99%
“…Estimating B 1 changed the temperature mainly for the lower and middle troposphere (1,000-600 hPa). Cumulus parameterization plays important role in GCMs to regulate clouds and OLD in TR (Miyakawa et al, 2018). As increased B 1 accelerated autoconversion, vapor and clouds remained for less time in the atmosphere.…”
Section: Journal Of Geophysical Research: Atmospheresmentioning
confidence: 99%
See 2 more Smart Citations